Evaluation of Thermal Spray Aluminum Coating Implementation Based on Procedure Qualification Test (PQT) Inspection Data for Offshore Steel Structures - Fitri Ani; Fardin Hasibuan; Dwi Cahyadi Putra (METALOGRAM, 2026)
Thermal Spray Aluminum (TSA) coating is widely applied for corrosion protection of offshore steel structures operating in aggressive marine environments. In practical offshore projects, the quality of TSA coating implementation is primarily verified through inspection activities conducted during Procedure Qualification Tests (PQT). In this study, an inspection-based evaluation of TSA coating implementation was performed using documented PQT inspection records obtained from an offshore steel structure, without additional laboratory testing. TSA coating was applied using a twin wire electric arc spray process, and coating quality was assessed based on dry film thickness (DFT) measurements recorded at five inspection points. The measured DFT values ranged from 216 µm to 357 µm, with an average thickness of 284.8 µm. To ensure general applicability, the thickness distribution was interpreted using inspection-derived statistical indicators, including a thickness uniformity index and coefficient of variation. The results indicate a uniform coating build-up and stable application characteristics typical of arc-sprayed aluminum coatings. It is concluded that PQT inspection data provide a practical and reliable basis for evaluating TSA coating implementation and thickness consistency in offshore steel structure applications.